Evidence-based digital tools for weight loss maintenance: the NoHoW project - Stubbs, R. James (2021)
© 2021 The Author(s) Published by S. Karger AG, Basel. This is an Open Access article licensed under the Creative Commons Attribution-NonCommercial-4.0 International License (CC BY-NC) (http://www.karger.com/Services/OpenAccessLicense), applicable to the online version of the article only. Usage and distribution for commercial purposes requires written permission.